Graphite oxide tribo-layer formation under boundary lubrication of diesel fuel. Issue 1 (February 2021) - Fuadi, Z; Kurniawan, R; Kanda, K; Adachi, K
Abstract: Friction and wear of mechanical components (such as engines) is controlled by some kind of boundary films (also referred to as tribo-layer). In some cases, such boundary film is formed on the contact interface due to a tribo-chemical process in the presence of liquid media. In this paper, we demonstrate the formation of graphite oxide tribo-layer on the contact interface of steel in the presence of diesel fuel liquid media. A Raman spectrometer was used to analyse the tribo-layer structure. Although the intensity is low, it is shown that the tribo-layer has a structure of graphite oxide, demonstrated by the presence of D band peak at approximately 1350 cm −1 and G band peak at approximately 1550 cm −1 in the Raman spectra. Such graphite solid films on the sliding surfaces have ability to control friction and wear. This finding demonstrates the possibility of in-situ formation of solid protective film of a tribo-pair components using the working fluid where the use of lubricants is restricted as they contaminate the working fluid.